THEOLOGICAL STUDY OF MATTHEW 28:19-20 AND ITS RELEVANCE TO THE ROLE OF THE CHURCH IN THE MINISTRY OF GOSPEL PREACHING - Johanes Witoro (International Journal of Innovative Technologies in Social Science, 2022)
The Ascension of the Lord Jesus to Heaven plays an important part in the Bible's history, as the disciples of the Lord Jesus seem afraid after being abandoned by the Lord Jesus. However, before the Lord Jesus ascended to heaven, he conveyed an important revelation in Matthew 28:19-20, which is called the “Great Commission” and became the key to the Lord Jesus' mandate. This study discusses the Great Commission of the Lord Jesus, this writing uses qualitative research by using literature studies and hermeneutical studies supported by appropriate books and sources. With the studies carried out it has been found that the Great Commission is a commandment given to the Disciples and passed on to all believers today.